Panopticon and Dramaturgy Concepts in the Implementation of Offline Learning Trials during the Covid-19 Period - Sudarmiani; Ibadullah Malawi; I Wayan Kertih; Sarwono (Jurnal Pendidikan dan Pengajaran, 2022)
Due to the COVID-19 pandemic, beginning in March 2020, the teaching and learning process must adapt and be conducted online by relying on technology and internet networks. However, there are numerous issues in the sector with online learning. During the COVID-19 pandemic, the government has enacted various regulations that govern school teaching and learning activities through offline learning trials (PTM). The study is implemented using regulations, supervision, and setting and displays efforts that are all developed following health guidelines. This study aims to analyze the role of panopticon and dramaturgy in the execution of limited offline learning trials. The research method employed is phenomenology research with a qualitative approach. Interview and observation approaches were used to collect data. Collecting, reducing, presenting, and drawing conclusions were all part of the data analysis process. The study's findings include the following: (1) The disciplinary mechanism for the PTM trial can be analyzed through the formation of respectful and obedient behavior of school residents in the application of health protocols, and the shape of the panopticon in the PTM trial can be analyzed through the front and back stages, impression management (impression management), and dramaturgy idealization according to health protocols; (2) dramaturgy can be analyzed through the front and back stages, impression management (impression management), and dramaturgy idealization according to health protocols.